Ḳidush Hashem - Reikh, Eitan (Resling, 2018)
From the Binding of Isaac to Martyrdom in Medieval Germany
Keywords: Judentum; Aschkenasim; Abrahams Opfer; Märtyrer; Suizid; Rabbinische Literatur; Geschichte Anfänge-1500